Aerodynamic Characteristic Optimization on The Design of Anti - Ship Missile for Indonesian Fast - Attack Boat - Dwiastuty, Fuji; Bura, Romie Oktovianus; Triharjanto, Robertus Heru (Indonesian Journal of Aerospace, 2019)
Missile is one of Indonesia 7 self – reliant main weapon system programs. Therefore research on the anti – surface ship missile system concept had been carried out at the Faculty of Defense Technology, Defense University. This research aims to abtain optimal design of anti – ship missile concept from previous research, i.e. 2 stages cruise missile with diameter of 0.36 m, total length of 5.19 m, cruise flight altitude of 17 m, and cruise flight speed of 0.88 Mach. The optimation is done on the missile’s aerodynamics characteristics to maximize its lift to drag ratio, which is one of the factor that determine the missile’s performance. Variables of nose cone shapes, number of wings, and body cross sections were chosen for evaluation of lift to drag ratio. The research found that nose cone shape did not affect the aerodynamic characteristics since the flight speed is subsonic. From the rest of the variables, it is found that the best configuration is missile with 2 wings with root length of 1.18 m, height of 0.79 m, and tip length of 0.71 m, elliptical body cross section, and the missile is to be flown at 6o angle of attack.